SIFAT ORGANOLEPTIK KUE BROWNIES DENGAN PENAMBAHAN RUMPUT LAUT (Eucheuma cottonii) - Nurwati Nurwati; Muhamad Hasdar (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2021)
Brownies are one type of snack that is liked by many people, both children and adults. The types of brownies on the market are generally high in sugar and low in fiber. Seaweed brownies are a snack alternative by increasing the fiber content. The main purpose of this study was to determine the effect of adding seaweed to the organoleptic characteristics of Brownies. In this study the addition of seaweed as the main factor was designed using a completely randomized design with a unidirectional pattern, the experimental models were B0 (0 grams), B1 (50 grams), B3 (100 grams), and B3 (150 grams). grams). The tests carried out were organoleptic tests (scoring and hedonic tests). The results of the scoring test on the parameters of color, aroma, taste, and texture resulted in significant differences in each treatment. The hedonic test showed that the most preferred sample for the overall parameter was brownies without the addition of seaweed with code B1. The samples of brownies with 50 grams, 100 grams, and 150 grams of seaweed were still accepted by the panelists with a range of likes and dislikes. The addition of 150 grams of seaweed on the color parameter is not preferred.